A Comparison of Classical TRIZ and OTSM-TRIZ in Dealing with Complex Problems. (2015) - Fiorineschi, Lorenzo; Frillici, Francesco Saverio; Rissone, Paolo
Abstract: A comparison between Classical TRIZ and OTSM-TRIZ is presented in order to evaluate differences in using either method when facing complex problems. The case study considered for this purpose is the development of a new type of Gondola for stratospheric ballooning, in which OTSM-TRIZ has been used in order to manage the complexity of the system. Considerations regarding methodologies have been then expressed and grouped into three topics of comparison, in which main differences between the assessed approaches have been listed and explained, identifying OTSM-TRIZ as a valid tool in facing complex problems.